2014
DOI: 10.3233/idt-130183
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent IT governance decision-making support framework for a developing country's public university

Abstract: Decision support systems (DSS) can be helpful tools in university's planning and management. Decision support systems can contribute to efficient exchange of information between experts, stakeholders, decision makers and laypeople. However, intelligent Information technology (IT) governance decision support system for public universities is yet to be thoroughly investigated. This is because IT governance (ITG) is just evolving as a new paradigm to take care the stakeholders' expectations in leveraging IT with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Qassimi, A. et al discussed the application of ITG in a public organization, particularly in a governmental organization of a developing country [2]. Some works expose critical challenges for ITG and demonstrate how intelligent systems can help face these challenges [29,30]. A public university in Malaysia served as a scenario for these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Qassimi, A. et al discussed the application of ITG in a public organization, particularly in a governmental organization of a developing country [2]. Some works expose critical challenges for ITG and demonstrate how intelligent systems can help face these challenges [29,30]. A public university in Malaysia served as a scenario for these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of this work conducted a systematic mapping to identify the perspectives most cited in the literature available on the theme ITG in public organizations. Studies [2,[24][25][26][27][28][29][30] are among those selected in the mapping. The mapping demonstrated that public organizations of developing countries cite perspectives similar to those found in this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estos continuos cambios en las tendencias tecnológicas han acelerado la necesidad de tener objetivos de tecnologías de información (TI) que estén alineados al logro de los objetivos de las universidades públicas [29]. Las TI son ahora un socio estratégico y el enfoque debe estar en la capacidad de uso de instalaciones de TI con las perspectivas correctas para reducir el temor hacia la inversión en TI en las partes interesadas [3].…”
Section: Introductionunclassified
“…Há diversas pesquisas empíricas que tratam sobre a GTI. Há estudos realizados sobre benefícios da TI e a relação com o desempenho empresarial (Albertin & Albertin, 2008); utilização dos critérios de efetividade da GTI (Sortica & Graeml, 2009); adoção das práticas de modelos de GTI (Barbosa, Araújo, & Torres, 2011;Tarouco & Graeml, 2011); gerenciamento e controle de operação (Luciano & Testa, 2011); mecanismos para melhorar o desempenho financeiro (Lunardi, Becker, & Maçada, 2012); revisão da literatura sobre recursos de TI sob as diferentes correntes de pesquisa e frameworks de governança (Hiekkanen et al, 2013); sistema de apoio à tomada de decisão inteligente (Arshad, Ahlan, & Ajayi, 2014); impactos gerados nos processos de trabalho (Klumb & Azevedo, 2014); ferramenta na gestão de negócios (Duarte, Kipper, Paz, & Mariani, 2015); resolução de conflitos e eficiência na implementação e consecução de objetivos de negócios em programas de TI (Parolia, Jiang, Chen, & Klein, 2015); análise da dimensão alinhamento estratégico nas Universidades Federais Brasileiras (Putz et al, 2017); e benefícios da TI para as estratégias empresariais (Moura et al, 2018).…”
Section: Introductionunclassified
“…Assim, tendo em conta esse cenário, a GTI concentra-se na realização e transformação de recursos para atender às demandas atuais e futuras do processo de negócio (foco interno) e clientes do negócio (foco externo). O controle exercido pelo Conselho de Administração e gerências, na formulação de decisões corretas, permite a criação de estruturas e processos que sustentem assim as melhores práticas, a fim de adaptá-las para permitir o alinhamento estratégico da TI com o negócio, garantindo que as organizações de TI possam estender suas estratégias e objetivos a uma utilização ótima de seus recursos, percebida por seus usuários gerenciados, levando a um bom desempenho corporativo (Arshad et al, 2014 A GTI tem despertado um crescente interesse acadêmico e profissional, pois evidencia a relevância e a evolução da TI na sociedade atual (Santos, 2018…”
Section: Introductionunclassified